Simulation of Minefield Installation in a Video Game Engine - Maksym Maksymov; Oleksii Neizhpapa; Oleksandr Toshev; Maksym Kiriakidi (Energy Engineering and Control Systems)
In the evolving world of modern digital gaming, particularly within tactical war-game strategies and realistic naval combat environments, the demand for accurate simulation and immersive experience is growing. The design and simulation of naval warfare must integrate more complex systems, including the impact of underwater minefield effectiveness. The research goal is to develop a framework and model that accurately predicts the tactical and operational impact of naval minefields on vessels across diverse gameplay scenarios. The simulation is designed to consider many variables, such as different mine and ship types, different landing strategies, varying environmental parameters and weather. The first objective of this research is to improve damage prediction algorithms, enabling the simulation to more accurately estimate the consequences of ships passing through a minefield. The second objective is to enhance mine allocation logic, developing algorithms that calculate the optimal quantity, type, and distribution of mines needed to halt or delay enemy advances.